(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2023)
This work with the title “Henry Thoreau and the Philosophy of Civil Disobedience as a non-catalytic and catalytic Model for Conflict Resolution” is anchored on the thesis which asserts that non-cooperation with evil is as much a moral obligation as cooperation with good. The research problem which this paper focuses on is to unravel how Thoreau exemplified the philosophy of civil disobedience. The major objective of this essay is to expose the essential definitive elements of the philosophy of civil disobedience. Consequently, this research employs the philosophical tools of exposition, analysis and criticism in its discourse of the subject matter. The research establishes that commitment to civil disobedience as a measure of conflict resolution must be activated from a conscience that is abrasive and nonconformist to evil. The conscience constitutes the highest law and obedience to its dictates confers authenticity on the human being as an indivisible moral entity. Every act of civil disobedience is targeted at disobeying unjust and oppressive laws and or social systems. It is a form of rebellion which calls for active noncompliance to the unjust system. Though most intellectuals affirm that non-violence must be a fundamental element in every act of civil disobedience, Thoreau views the deployment of violence in overcoming injustice as a complementary element of civil disobedience. The use of violence as means to undo evil in the society is however a last resort in Thoreau’s scheme. It is this infusion of violence in the act of civil disobedience which appears to make Thoreau’s thought clash with the logic of consistency since civil disobedience is mostly acclaimed to be a non-violent act of resistance to evil. In submission, it can be gleaned that Thoreau advocated for non-violent civil disobedience only when the oppressive and unjust system is non-recalcitrant to change and transformation. However, when the evil system is totally opposed to change, then Thoreau would subscribe to the employment of a catalytic means to resist the evil system.